Effects of Ransomware: Analysis, Challenges and Future Perspective: Rabia Mehmood - Rabia Mehmood (International Journal for Electronic Crime Investigation, 2023)
This review paper highlights the challenges and best practices in malware analysis, specifically focusing on the age of ransomware. It provides an overview of malware and its impact on computer systems and user privacy by lists various types of malware, including viruses, Trojans, spyware, adware, worms and highlights major malware attacks including the methods used and the resulting damages. Further, the article explores the challenges faced in ransomware analysis, including advanced encryption and evasion techniques, anti-analysis mechanisms, zero-day exploits and vulnerabilities, polymorphic and dynamic behavior, lack of resources, complexity of ransomware, collaboration difficulties, and cost implications. These challenges make it necessary for security researchers to constantly update their knowledge and techniques to effectively analyze ransomware. This study concludes best practices for ransomware analysis including isolating and segmenting ransomware samples in controlled environments, emphasizing behavior analysis and threat hunting, investing in advanced reverse engineering and automated analysis techniques, promoting collaborative intelligence and information sharing, and implementing security measures to protect against ransomware attacks. Additionally, the article briefly mentions static analysis techniques which explains that static analysis involves examining malware files and code without executing them. It can be used to identify ransomware characteristics, such as encryption algorithms, ransom demands, remote command execution, and obfuscation techniques. Moreover, file and code analysis methods, signature-based detection, code deobfuscation and unpacking techniques, and malicious document analysis and exploit detection are also suggested as part of static analysis.